已知函数 $f(x)=\ln x+a-1, a \in \mathbf{R}$.
(I) 若 $f(x) \leqslant x$, 求 $a$ 的取值范围;
(II) 当 $a \in(0,1]$ 时, 证明: $f(x) \leqslant \frac{(x-1) \mathrm{e}^x}{\mathrm{e}^a}$.
【答案】 解: (I) 记 $g(x)=f(x)-x=\ln x-x+a-1$.
则 $g(x) \leqslant 0$ 恒成立, 即 $g(x)_{\text {max }} \leqslant 0$.
$\cdots \cdots 1$ 分
$\because g^{\prime}(x)=\frac{1-x}{x}, \therefore g(x)$ 在 $(0,1)$ 上单调递增, 在 $(1,+\infty)$ 上单调递减. $\quad \cdots \cdots 3$ 分
$\therefore g(x)_{\max }=g(1) \leqslant 0$. 解得 $a \leqslant 2$.
$\therefore$ 实数 $a$ 的取值范围是 $(-\infty, 2]$.
$\cdots \cdots 5$ 分
(II ) 记 $h(x)=\frac{(x-1) \mathrm{e}^x}{\mathrm{e}^a}-f(x)=\frac{(x-1) \mathrm{e}^x}{\mathrm{e}^a}-\ln x+1-a(x > 0)$.
$\because h^{\prime}(x)=x \mathrm{e}^{x-\alpha}-\frac{1}{x}, h^{\prime}(x)$ 在 $(0,+\infty)$ 上单调递增.
$\cdots \cdots 6$ 分
由 $a \in(0,1]$, 知 $h^{\prime}\left(\frac{1}{2}\right)=\frac{1}{2} \mathrm{e}^{\frac{1}{2}-a}-2 < 0, h^{\prime}(1)=\mathrm{e}^{1-a}-1 \geqslant 0$.
$\therefore \exists x_0 \in\left(\frac{1}{2}, 1\right], h^{\prime}\left(x_0\right)=0$. 即 $x_0 \mathrm{e}^{x_0-a}=\frac{1}{x_0} . \quad \cdots(*)$
$\therefore$ 当 $x \in\left(0, x_0\right), h^{\prime}(x) < 0, h(x)$ 单调递减; 当 $x \in\left(x_0,+\infty\right), h^{\prime}(x) > 0, h(x)$ 单调递增.
$\therefore h(x)_{\min }=h\left(x_0\right)=\left(x_0-1\right) \mathrm{e}^{x_0-a}-\ln x_0+1-a . \quad \cdots(* *) \quad \cdots \cdots 8$ 分
由 (*) 式, 可得 $\mathrm{e}^{x_0-a}=\frac{1}{x_0^2}, x_0-a=-2 \ln x_0$.
代人 $(* *)$ 式, 得 $h\left(x_0\right)=\frac{x_0-1}{x_0^2}-3 \ln x_0-x_0+1$.
由 (I) 知, 当 $a=2$ 时有 $\ln x \leqslant x-1$, 故 $-\ln x_0 \geqslant 1-x_0$.

$$
\therefore h\left(x_0\right) \geqslant \frac{x_0-1}{x_0^2}-3\left(x_0-1\right)-x_0+1=\frac{\left(1-x_0\right)\left(2 x_0-1\right)\left(2 x_0+1\right)}{x_0^2} \text {. }
$$
由 $x_0 \in\left(\frac{1}{2}, 1\right], \therefore h\left(x_0\right) \geqslant 0$.
故 $h(x) \geqslant 0$, 即 $f(x) \leqslant \frac{(x-1) \mathrm{e}^x}{\mathrm{e}^a}$, 原不等式得证.


系统推荐